The Association between Female Reproductive Factors and Open-Angle Glaucoma in Korean Women: The Korean National Health and Nutrition Examination Survey V - Yong Un Shin; Eun Hee Hong; Min Ho Kang; Heeyoon Cho; Mincheol Seong (Journal of Ophthalmology)
Purpose. We investigated associations between female reproductive factors and open-angle glaucoma (OAG) in Korean females using the Korea National Health and Nutrition Examination Survey (KNHANES). Methods. A nationwide, population-based, cross-sectional study was conducted. We enrolled 23,376 participants from the KNHANES who had undergone ophthalmologic exams from 2010 through 2012. Associations between undiagnosed OAG and female reproductive factors such as age at menarche and menopause, parity, history of lactation, and administration of oral contraceptives (OC) or hormone replacement therapy (HRT) were determined using stepwise logistic regression analyses. Results. Of the enrolled participants, 6,860 participants (397 with OAG and 6,463 without OAG) met our study criteria and were included in the analyses. In the multivariate logistic regression analysis after adjusting for all potential confounding factors, only early menopause (younger than 45 years) was significantly associated with OAG in participants with natural menopause (OR 2.28, 95% CI 1.17–4.46). Age at menarche, parity, history of lactation, and administration of OC or HRT were not significantly associated with OAG. Conclusions. Only early menopause was associated with an increased risk of OAG in our study, in contrast to previous Western studies reporting both early menopause and late menarche as associated factors.